Overcome divisions and confront threats: Memo to the presidents of the European Commission, council and parliament - Maria Demertzis; André Sapir; Jeromin Zettelmeyer (Bruegel, 2024)
In the last five years, the European Union managed to find its way through a series of major shocks, including the pandemic and the 2022 surge in energy prices. The response was in many ways remarkable, including unprecedented EU borrowing to fund the NextGenerationEU economic recovery programme and a coordinated reduction in energy demand. However, these crises have left the EU in a bruised state. The pandemic recession and energy-support measures have squeezed fiscal space. Higher energy prices have persisted and EU industrial competitiveness has been eroded. The productivity and per-capita income gap with the United States has widened. Meanwhile, the world around the EU has become more threatening and fragmented. The military situation in Ukraine remains precarious. China has become both more authoritarian and more assertive. The US shift toward protectionism has become entrenched. There is less consensus for measures to combat climate change. In the face of all this, the challenges confronting you are substantial. In the next five years, you must continue to support Ukraine while implementing measures to reinvigorate EU growth, meet the 2030 climate targets and lay the ground for meeting the 2040 goals, and secure faster emissions reductions beyond the EU's borders. Social cohesion needs to be restored to head off threats to the EU model. More needs to be done to improve EU external security. Promoting growth and enhancing cohesion will entail further deepening of the single market in areas with the highest growth impact, doing more to support innovation and defending competition, openness and multilateralism. Safeguarding the European Green Deal means boosting green industrialisation and fair burden-sharing, while scaling up international climate finance. Strengthening security requires continued support for Ukraine and the addressing of economic security risks. Underpinning all of this, a serious effort must be made to improve EU governance - and it must be done without creating further division.
Keywords: 330; eu budget; eu governance; european commission; european monetary union; climate change